2012
DOI: 10.1016/j.molcel.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Essential Features and Rational Design of CRISPR RNAs that Function with the Cas RAMP Module Complex to Cleave RNAs

Abstract: SUMMARY Small RNAs target invaders for silencing in the CRISPR-Cas pathways that protect bacteria and archaea from viruses and plasmids. The CRISPR RNAs (crRNAs) contain sequence elements acquired from invaders that guide CRISPR-associated (Cas) proteins back to the complementary invading DNA or RNA. Here, we have analyzed essential features of the crRNAs associated with the Cas RAMP module (Cmr) effector complex, which cleaves targeted RNAs. We show that Cmr crRNAs contain an 8-nucleotide 5’ sequence tag (als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
315
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(333 citation statements)
references
References 42 publications
12
315
1
1
Order By: Relevance
“…In such cases, targeting the DNA would counterselect against the transferred CRISPR-Cas as it will kill the host. However, elimination of the resistance element can still be achieved using CRISPR-Cas system that target RNA (12,24,25). Although targeting the RNA will eliminate the resistance conferred by the encoded gene, it will not kill the pathogen and would thus avoid counterselection against the delivering temperate phage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, targeting the DNA would counterselect against the transferred CRISPR-Cas as it will kill the host. However, elimination of the resistance element can still be achieved using CRISPR-Cas system that target RNA (12,24,25). Although targeting the RNA will eliminate the resistance conferred by the encoded gene, it will not kill the pathogen and would thus avoid counterselection against the delivering temperate phage.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR-Cas systems have also recently been used to phenotypically correct genetic diseases in live animals (11), and their utility is being explored for various therapeutic approaches in mammals. Nevertheless, only limited studies have shown the use of CRISPR-Cas systems to target antibiotic resistance genes or a specific population of virulent bacterial strains (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Guide sequences in P. furiosus CRISPRs are generally 37 nucleotides long, and including the 8 nucleotide tag, are 45 nucleotides long. In contrast, the 39-nt species still possesses the 8 nucleotide tag, but lacks 6 nucleotides of the guide sequence at the 3 end [65].…”
Section: Potential For Therapies Based On the Crispr-cas Systemmentioning
confidence: 99%
“…For a prokaryote that lacks Cmr genes, these can easily be introduced in a single operon along with the engineered crRNA. This opens up potential avenues for microorganism customization and research into gene functions [65].…”
Section: Potential For Therapies Based On the Crispr-cas Systemmentioning
confidence: 99%
See 1 more Smart Citation